Breakfast at Tiffany's [videorecording (DVD)] - Mancini, Henry (Paramount centennial collection., 2017)
Holly Golightly is a carefree New York playgirl who is scouring Manhattan looking for a suitable millionaire to marry. However, when Paul Varjak, a struggling young writer, moves into her apartment building, she becomes interested in him. Paul gets swept into Holly's dizzying, delightfully unstructured lifestyle.